Reflexivity in Meadow Mari: Binding and Agree1. (April 2017) - Volkova, Anna
Abstract: According to the Canonical Binding Theory (Chomsky 1981), anaphors must be bound in their local domain and pronominals must be free. The discovery of "long‐distance anaphors" (e.g. Thrainsson 1976, Giorgi 1984), which violate the locality condition, induced the search for independent criteria. Giorgi (1984:310) proposed a widely adopted criterion: "pronouns can have split antecedents and anaphors cannot". Recent minimalist binding theories derive this property of anaphors from the way a dependency on the antecedent is established which makes it intrinsic to binding. However, this leads to an important problem, since some languages have elements that i) may be locally bound and, hence, look like anaphors; yet ii) allow split antecedents which is a property of pronouns (e.g. Japanese and Korean, Katada 1991, Kasai 2000). In this paper I analyze the data of another such language, namely Meadow Mari (Uralic), and show that such facts require a modular approach to binding (see Reuland 2011). I further argue that here the left periphery contains the relevant factor.